2015
DOI: 10.1016/j.tust.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The excavation of a circular tunnel in a bedded argillaceous rock (Opalinus Clay): Short-term rock mass response and FDEM numerical analysis

Abstract: a b s t r a c tThe Opalinus Clay formation is currently being investigated as a potential host rock for the deep geological disposal of radioactive waste in Switzerland. Recently, a test tunnel was excavated at the Mont Terri underground rock laboratory (URL) as part of a long-term research project (''Full-scale Emplacement (FE) experiment'') aimed at studying the thermo-hydro-mechanical (THM) effects induced by the presence of an underground repository. The objective of this paper is twofold. Firstly, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(52 citation statements)
references
References 31 publications
1
47
0
Order By: Relevance
“…Loess, which is derived from unconsolidated materials (Zhu, 2012), is sensitive to sliding upon wetting and being broken down due to its metastable structure (Wen and Yan, 2014). Loess has a significant character of randomly open and loose particle with high porosity (Tonon, 2011;Graziani and Boldini, 2012;Ng et al, 2012;Lisjak et al, 2015;Smalley and Derbyshire, 1991;Assallay et al, 1997;Jefferson et al, 2004). When a large span tunnel or underground space is constructed in loess ground, it inevitably disturbs the in situ stress field, and then causes large ground displacements (Sharifzadeha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Loess, which is derived from unconsolidated materials (Zhu, 2012), is sensitive to sliding upon wetting and being broken down due to its metastable structure (Wen and Yan, 2014). Loess has a significant character of randomly open and loose particle with high porosity (Tonon, 2011;Graziani and Boldini, 2012;Ng et al, 2012;Lisjak et al, 2015;Smalley and Derbyshire, 1991;Assallay et al, 1997;Jefferson et al, 2004). When a large span tunnel or underground space is constructed in loess ground, it inevitably disturbs the in situ stress field, and then causes large ground displacements (Sharifzadeha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A motivation is to combine advantages of both continuous and discontinuous approaches proposed by Munjiza et al (1995), Li et al (2004), Wang et al (2013), etc. These combined methods include FDEM (FEMDEM) (Munjiza et al, 1995;Munjiza, 2004;Mahabadi et al, 2010Mahabadi et al, , 2012Lisjak et al, 2014Lisjak et al, , 2015 and Continuous-Discontinuous Element Method (CDEM) (Li et al, 2004(Li et al, , 2008Ma et al, 2011;Wang et al, 2013;Li et al, 2015). In the study of Cai et al (2007), the continuum-based software FLAC was coupled with the discontinuum-based software PFC to investigate acoustic emissions in large-scale underground excavations.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…In the study of Cai et al (2007), the continuum-based software FLAC was coupled with the discontinuum-based software PFC to investigate acoustic emissions in large-scale underground excavations. Lisjak et al (2015) used the FDEM method to model the crack evolution due to the excavation of a circular tunnel in a bedded argillaceous rock. The progressive failure of rock masses was simulated by a cohesivezone approach (Munjiza et al, 1995;Munjiza, 2004;Mahabadi et al, 2010Mahabadi et al, , 2012Lisjak et al, 2014Lisjak et al, , 2015.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…By three axial compression test, Nguyen T S et al [6][7][8][9] established the argillite constitutive model, and revealed the relationship between mechanical parameters of slate such as peak strength and elastic modulus and confining pressure, moisture content and jointed relationship, proof the slate rock has anisotropic mechanical characteristics, and proved that the slate rock mass has anisotropic mechanical characteristics. In the slate rock tunnel stability, Lisjak A et al [10,11], by using the numerical analysis software, for the excavation of slate tunnel with different stratification plane directions, carried out numerical analysis, explained the characteristics of stratification plane direction effecting on the stability of the tunnel. Su Zhendao [12], in the deformation and stress analysis of the tunnel lining, based on the field test of the argillite tunnel, he recommended that the radial grouting behind the lining of the tunnel should be taken to reduce the pressure of the lining so as to enhance the stability of surrounding rock.…”
Section: Introductionmentioning
confidence: 99%